Mobile social media marketing: a partial least squares structural equation modelling approach - Yap, Wei-Chyi; Garry, Wei-Han Tan (2017)
The revolution of mobile technologies has brought various innovations to humankind. Mobile social media marketing (m-SMM) is an emerging innovation in marketing communication channel with benefits for sellers. Therefore, the study determines to recognise the elements contributing to the adoption of m-SMM. The study adapted combined models such as unified theory of acceptance and use of technology (UTAUT), uses and gratification (U&G), diffusion of innovation (DOI) and extended the framework with training and support (TS). The data were derived from 213 Malaysian sellers through self-administered questionnaire and analysed using partial least squares structural equation modelling (PLS-SEM) approach. Results proved to be significant on all constructs tested on behavioural intention (BI) except performance expectancy (PE), effort expectancy (EE) and entertainment (ET). The findings could be useful for scholars, researchers and mobile marketers in the area of m-SMM.